Exploring Policy Interventions to Support the Introduction of Autonomous Vehicles in Indonesia - Wiedyanoe, Sandhi; Fonzone, Achille; Cowie, Jonathan; Utomo, Dhanan Surwo (Sekolah Tinggi Ilmu Kepolisian, 2024)
This paper aims to analyze policy interventions regarding the implementation of autonomous vehicles (AV) in Indonesia. The research takes place in Jakarta due to its unique characteristics and status as one of the most congested cities in the world. The paper employs the qualitative approach to understand policy intervention for AV implementation. The methods used in this research are the combination of Focus Group Discussions (FGDs) and Semi-Structured Interview. This research elaborates that AV implementation in Indonesia should come in the form of AV buses in the initial stage. Thus, it is necessary in the context of AV buses to construct dedicated lanes, provide onboard stewards, and give government incentives in a way that ensures the adoption's success rate. Furthermore, the thematic analysis of the research also emphasizes several themes in the context of AV implementation, such as implementation, accessibility, regulatory framework, sustainability, local characteristics, and annotation. These themes could provide a comprehensive understanding related to the policy intervention that should be taken by the Indonesian government regarding the AV implementation in Indonesia.